(untitled) (Journal of Economic Research & Business Administration, 2016)
The company’s oil and gas sector within the scope of work and complexity of need to use not only General but also specific requirements of specific standards. The oil and gas industry is one of those global industries that are global in nature. Facing industry challenges geopolitical and environmental concerns with energy supply and natural resources in combination with the often observed complex relationships between companies and stakeholders suggest the need to apply the transition to IFRS a number of complex judgments relating to methods of implementing new standards. This article examined methods of reporting in accordance with IFRS in the oil and gas industry. And also presented a vision of how companies respond to various challenges faced by the industry challenges faced by entities when applying IFRS.